The Specific Applications of Yantras and Shastras: A Literary Review and Recent Developments in Shalya Tantra - Prasad M Bharamanaikar; Kubendra H Pachchinavar; R.C Yakkundi (AYUSHDHARA, 2025)
Ayurveda is an eternal science that existed in the universal consciousness. Aim of Ayurveda is the maintenance of health in a healthy man and relief from disease in patients. The Ayurveda categorised into eight branches (Astangas of Ayurveda) and among some branches deals with different equipments and instruments (Yantras and Shastras) for different therapeutic purposes. These Yantras and Shastras are mainly used in surgical and parasurgical procedures. The surgical activities (Shastra karma) are of eight kinds viz Chedhana, Bhedhana, Lekhana, Vedhana, Eshana, Aharana, Visravana and Seevana requires utilisation of different yantras and Shastras. Ancient acharyas gives their opinion about the number of Yantras, shastras, Anushastras, etc, according to their view. According to Acharya Sushruta there are 101 Yantras, 20 Shastras, 25 Upayantras and 14 Anushastras. These are the major equipments used in Ayurveda surgery. The development has seen for any surgical operation major/minor in terms of surgical instruments (blunt/Sharp) Patients preparation requirements and operation theatre equipment and drugs required for anaesthesia, sterilization requirements, medicine, etc.